SOSIALISASI TRI DHARMA PERGURUAN TINGGI: STRATEGI MENINGKATKAN MINAT STUDI LANJUT PADA SISWA SMK - Rizki Prakasa Hasibuan; Nofri Yudi Arifin; Hamdani Jumardi; Ardila Wulandari; Tasya Bintang Rahmadea (PUAN INDONESIA, 2026)
This community service activity was carried out to increase the understanding and motivation of vocational school students regarding the importance of pursuing higher education through the introduction of the Tri Dharma of Higher Education. The Tri Dharma consists of three pillars: education and teaching, research, and community service, which are the main foundations for the operation of universities. The method used was participatory socialization involving 20 students from grades XI and XII of SMK X in Batam City, Riau Islands. The activity used an interactive approach with presentations, question-and-answer sessions, and group discussions. The results showed a significant increase in students' understanding of the Tri Dharma from 28% to 84% after the socialization. In addition, 88% of participants stated that they were more motivated to continue their studies to higher education after participating in this activity, with 80% evaluating that the activity provided new and beneficial insights. The findings indicate that participatory socialization is effective in bridging the knowledge gap between vocational secondary education and higher education. This community service activity demonstrates that the socialization of the Tri Dharma of Higher Education is an effective strategy in increasing students' understanding and motivation to pursue higher education, while strengthening collaboration between universities and vocational schools in preparing quality human resources.